Modified adaptive differential evolution based optimal operation and security of AC-DC microgrid systems - Bharothu, Jyothilal Nayak; Sridhar, M.; Rao, R. Srinivasa (International journal of electrical power & energy systems, 2018)
•A novel approach is proposed to formulate OPF problem on AC-DC microgrids as a traditional AC OPF problem.•A modified adaptive differential evolution algorithm is proposed for solving the non-convex AC-DC OPF problem.•To tackle the converter equations, the AC and DC side buses of each converter are merged to have an equivalent AC bus in the system.•Simulations are carried out on the IEEE 30-and 39-bus systems connected to 6-bus and 9-bus DC microgrids to illustrate the proposed approach. The recent advancement in power electronic systems has enabled the formation of AC-DC microgrids by integration of DC microgrids into conventional AC grid. In this paper, an approach for optimal power flow (OPF) problem formulation in AC-DC microgrid networks is proposed. In the formulated AC-DC microgrid OPF problem, the objective functions considered for minimization are the total cost of generation in both the AC and DC networks and the cost of active power transfer from the AC grid to the DC microgrid. The OPF problem is subject to the limits of voltage magnitudes, power flows, and the AC-DC power electronic converter's limits. This paper also presents an approach to reformulate the nonlinear AC-DC OPF problem as an equivalent traditional AC OPF problem. A modified adaptive differential evolution algorithm is proposed to solve the non-convex AC OPF problem, Simulation studies are performed on an IEEE 30-bus and IEEE 39-bus test system connected to 6-bus and 9-bus DC microgrids under both normal operation and network contingency conditions. The results obtained on the test systems by the proposed approach confirm the validity of the developed approach.